2018
DOI: 10.1111/cote.12342
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic studies of the adsorption behaviour of the natural dye cochineal on polyamide 66

Abstract: The adsorption behaviour of the natural dye cochineal on polyamide 66 was studied at different pH values. The thermodynamic and kinetic parameters such as standard affinity (−Δμ˚), changes in enthalpy (ΔH˚) and entropy (ΔS˚), diffusion coefficient and activation energy of the diffusion, were determined for pH values of 3 and 6. Results indicated that the experimental data fitted appropriately with the Nernst isotherm. Furthermore, the partitioning ratio and −Δμ˚ decreased significantly with increasing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(57 reference statements)
2
9
0
Order By: Relevance
“…These data suggested that the mechanism of adsorption of the pseudo second-order model was predominant and that the overall rate of adsorption of cochineal dye was probably controlled by the chemisorption process due to the electrostatic attraction between the dye and the fiber. This is consistent with other studies that described the adsorption of the cochineal dye in compounds having amine groups, such as wool 28,43 and polyamide, 6 and in the marine sponge Hippospongia communis that has protein composition. 44…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These data suggested that the mechanism of adsorption of the pseudo second-order model was predominant and that the overall rate of adsorption of cochineal dye was probably controlled by the chemisorption process due to the electrostatic attraction between the dye and the fiber. This is consistent with other studies that described the adsorption of the cochineal dye in compounds having amine groups, such as wool 28,43 and polyamide, 6 and in the marine sponge Hippospongia communis that has protein composition. 44…”
Section: Resultssupporting
confidence: 92%
“…The small amount of dye adsorbed in the dyeing of untreated fabric can be attributed to the formation of non-electrostatic interactions as hydrogen bonds between the hydroxyl groups present in the dye and cellulose and also by the attraction of Van der Waals forces. 6,38…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations